Promoting the Transformation of Li2S2 to Li2S: Significantly Increasing Utilization of Active Materials for High‐Sulfur‐Loading Li–S Batteries. Issue 25 (7th May 2019) - Yang, Xiaofei; Gao, Xuejie; Sun, Qian; Jand, Sara Panahian; Yu, Ying; Zhao, Yang; Li, Xia; Adair, Keegan; Kuo, Liang‐Yin; Rohrer, Jochen; Liang, Jianneng; Lin, Xiaoting; et al.
Abstract: Lithium–sulfur (Li–S) batteries with high sulfur loading are urgently required in order to take advantage of their high theoretical energy density. Ether‐based Li–S batteries involve sophisticated multistep solid–liquid–solid–solid electrochemical reaction mechanisms. Recently, studies on Li–S batteries have widely focused on the initial solid (sulfur)–liquid (soluble polysulfide)–solid (Li2 S2 ) conversion reactions, which contribute to the first 50% of the theoretical capacity of the Li–S batteries. Nonetheless, the sluggish kinetics of the solid–solid conversion from solid‐state intermediate product Li2 S2 to the final discharge product Li2 S (corresponding to the last 50% of the theoretical capacity) leads to the premature end of discharge, resulting in low discharge capacity output and low sulfur utilization. To tackle the aforementioned issue, a catalyst of amorphous cobalt sulfide (CoS3 ) is proposed to decrease the dissociation energy of Li2 S2 and propel the electrochemical transformation of Li2 S2 to Li2 S. The CoS3 catalyst plays a critical role in improving the sulfur utilization, especially in high‐loading sulfur cathodes (3–10 mg cm −2 ). Accordingly, the Li2 S/Li2 S2 ratio in the discharge products increased to 5.60/1 from 1/1.63 with CoS3 catalyst, resulting in a sulfur utilization increase of 20% (335 mAh g −1 ) compared to the counterpart sulfur electrode without CoS3 . Abstract : Amorphous CoS3 are developed to promote the solid–solid conversion from solid‐state intermediate product Li2 S2 to the final discharge product Li2 S, which significantly increased the sulfur utilizations for over 20% for high loading electrodes.